THE EFFECT OF REAP STRATEGY ON READING COMPREHENSION - Andarini Permata Cahyaningtyas (Jurnal Pendidikan dan Pengajaran, 2017)
The purposes of this study are to find out the effect of REAP strategy on reading comprehension of the fifth grade elementary students of third cluster of Kotagede Yogyakarta. The research method in this study is quasi-experimental with Pretest-Posttest Control Group Design. The population was all of fifth grade elementary students of third cluster of Kotagede Yogyakarta. The sample was fifth grade students of SD Baluwarti, SD Kotagede 1, and SD Kotagede 5 Yogyakarta that were establised by cluster random sampling technique. The data were collected using tests. The validity of the instrument was measured in terms of content and construct validity. The reliability of the instrument was stated good with the score of Cronbach’s Alpha = 0,734. The result data of this study were analized by independent sample t-test and Manova with Hotteling’s Trace formula. The result showed that REAP strategy gave a positive and significant effect on reading comprehension that is proved by the score of t-test = 4,914 and 3,286 with sig = 0,000 and 0,002. Based on the result, it can be concluded that REAP strategy give positive and significant effect on reading comprehension of fifth grade elementary student of third cluster of Kotagede Yogyakarta.